Uma arquitetura multiagente para gerenciamento de dispositivos em ambientes da internet das coisas - Cagnin, Renato Luciano [UNESP] (2015)
The Internet of Things (IoT) is the term used to define the new Internet scenario, characterized by connecting a variety of devices that have wireless communication interfaces and are immersed in a physical environment. The IoT environments are open, where new components can be incorporated; distributed, characterized by several components networked; and dynamic. These characteristics bring many challenges for the development of applications that seek to access, integrate and analyze the amount of data produced by these devices. In this sense, this paper proposes a software architecture for the development of applications in the context of IoT. The proposed architecture is made up of several layers characterized by different technologies. The technologies used are Multi-Agent Systems, Service Oriented Architecture and Web Semantics. To demonstrate the feasibility of the proposal, a prototype of the architecture was developed and applied in a case study in the context of home automation. The results presented show that the architecture demonstrated ability to identify different devices, operations, and services; and coordinate the executions of operation of devices in more complex tasks according to the available contextual information